WHEN THE WALL SPEAKS: SOCIAL SEMIOTICS ANALYSIS OF (COVID-19)-THEMED MURALS IN INDONESIA - Hariyatmi, Sri (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
This study aims at analyzing how the meaning-making of semiotic signs is manifested on (Covid-19)-themed murals in Indonesia. Four murals with covid-19 themes derived from different sources on the Indonesian website were used as the main data for this study. Drawing on Kress and van Leeuwen’s representational, interactive, and compositional function of social semiotics, the analysis reveals that (1) the murals adopt the four processes in narrative representation, (2) the gazes are categorized as offers images and the use of long shot in the images suggest objectivity and social distance, (3) the messages are delivered in given-new and real-ideal pattern and the absence of frames in the murals indicating that the visual and verbal modes lock together to create the sense of unity between the image and written modes to construct and deliver the message by integrating the existing knowledge to reinforce new information. Thus, the current study contributes to the multimodal studies of how visual and written expression construct the meaning-making process.